Measuring CP violation and B0 s-B̄0 s mixing using B0 s → J/ψφ with φ → K+K-, J/ψ → μ+μ- - Azfar, F; Huffman, T; Lyons, L; Reichold, A; Waters, D (2000)

(untitled)
We present a preliminary study of a new technique for measuring B0s mixing and CP violation using the decay B0s → J/ψφ, φ K+K-, J/ψ → μ+μ-. This technique utilizes the unequal lifetimes of the B0s CP even and odd eigenstates, and an angular variable decomposition of the CP content of the final state. This study is based on CDF Run-I observations and Run-II projections, and predicts that the B0s mixing parameter cursive Greek chis can be measured with high accuracy in untagged samples if this approach is adopted. A large CP asymmetry may also be possible to measure. The accuracy of this method is shown to increase for higher values of cursive Greek chis as the lifetime splitting of the CP eigenstates increases. The measurement of cursive Greek chis does not depend on tagging, whereas the observation of a CP-violating asymmetry does.